Proof of concept and early development stage of market-oriented high iron and zinc rice expressing dicot ferritin and rice nicotianamine synthase genes - Tsakirpaloglou, Nikolaos; Bueno-Mota, Gela; Soriano, Jessica Candace; Arcillas, Erwin; Yu, Su-May; Bouis, Howarth E.; Arines, Felichi Mae; Stangoulis, James; Trijatmiko, Kurniawan Rudi; Reinke, Russell; Tohme, Joseph; Slamet-Loedin, Inez H. (Nature Publishing Group, 2023)
Micronutrient deficiencies such as iron (Fe), zinc (Zn), and vitamin A, constitute a severe global public health phenomenon. Over half of preschool children and two-thirds of nonpregnant women of reproductive age worldwide have micronutrient deficiencies. Biofortification is a cost-effective strategy that comprises a meaningful and sustainable means of addressing this issue by delivering micronutrients through staple foods to populations with limited access to diverse diets and other nutritional interventions. Here, we report on the proof-of-concept and early development stage of a collection of biofortified rice events with a high density of Fe and Zn in polished grains that have been pursued further to advance development for product release. In total, eight constructs were developed specifically expressing dicot ferritins and the rice nicotianamine synthase 2 (OsNAS2) gene under different combinations of promoters. A large-scale transformation of these constructs to Bangladesh and Philippines commercial indica cultivars and subsequent molecular screening and confined field evaluations resulted in the identification of a pool of ten events with Fe and Zn concentrations in polished grains of up to 11 μg g−1 and up to 37 μg g−1, respectively. The latter has the potential to reduce the prevalence of inadequate Zn intake for women of childbearing age in Bangladesh and in the Philippines by 30% and 50%, respectively, compared to the current prevalence. To our knowledge, this is the first potential biotechnology public-sector product that adopts the product cycle phase-gated approach, routinely applied in the private sector.